Modeling, optimizing and simulating robot calibration with accuracy improvement - Motta, José Maurício Santos Torres (1999)
This work describes techniques for modeling, optimizing and simulating calibration processes ofrobots using off-line programming. The identification of geometric parameters of the nominalkinematic model is optimized using techniques of numerical optimization of the mathematicalmodel. The simulation of the actual robot and the measurement system is achieved by introducingrandom errors representing their physical behavior and its statistical repeatability. An evaluationof the corrected nominal kinematic model brings about a clear perception of the influence ofdistinct variables involved in the process for a suitable planning, and indicates a considerableaccuracy improvement when the optimized model is compared to the non-optimized one.